Lifetime stress and war exposure timing may predict methylation changes at NR3C1 based on a pilot study in a warrior cohort in a small‐scale society in Kenya. Issue 4 (14th October 2020) - Straight, Bilinda; Fisher, Georgiana; Needham, Belinda L.; Naugle, Amy; Olungah, Charles; Wanitjirattikal, Puntipa; Root, Cecilia; Farman, Jen; Barkman, Todd; Lalancette, Claudia
Abstract: Objectives: Candidate gene methylation studies of NR3C1 have identified associations with psychosocial adversity, including war trauma. This pilot study (sample sizes from 22 to 45 for primary analyses) examined NR3C1 methylation in a group of Kenyan pastoralist young men in relation to culturally relevant traumatic experiences, including participation in coalitional lethal gun violence. Methods: Adolescent and young adult Samburu men ("warriors") were recruited for participation. DNA was obtained from whole saliva and methylation analyses performed using mass spectrometry. We performed a data reduction of variables from a standardized instrument of lifetime stress using a factor analysis and we assessed the association between the extracted factors with culturally relevant and cross‐culturally comparative experiences. Results: Cumulative lifetime trauma exposure and forms of violence to which warriors are particularly susceptible were associated with DNA methylation changes in the NR3C1 1F promoter region but not in the NR3C1 1D promoter region. However, sensitivity analyses revealed significant associations between individual CpG sites in both regions and cumulative stress exposures, war exposure timing, and war fatalities. Conclusions: This study supports the importance of NR3C1 methylation changes in response to challenging life circumstances, including in a global south cultural context that contrasts in notable ways from global north contexts and from the starkly tragic examples of the Rwandan genocide and war‐associated rape explored in recent studies. Timing of traumatic exposure and culturally salient means to measure enduring symptoms of trauma remain important considerations for DNA methylation studies.